Upaya Meningkatkan Hasil Belajar IPA Melalui Strategi Multiple Inteligences - Yenni Marwah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study is motivated by the low ability of grade IV SD Parakan students in science lessons on subject matter Force. The purpose of this study is improving the learning process and improving students' ability in science lessons on Force subject matter through applying multiple intelligence approaches. The method used was the Classroom Action Research and it was carried out in two cycles. Based on the data analysis, the ability of students after the research action increases in each cycle. The highest score changes at each stage, from 80 to 90 and finally to 95; the lowest value has increased from 45 before the action and in cycle I to 45 at the end of the second cycle. The average value also increased from the initial 63.3; to 70.5; then 75.2. While the increasing in presentation of minimal completeness criteria achievement was initially 45.2%, to 65.6%, and finally to 81.3%. The observation results show that science learning activities by using Multiple Intelligences strategy in Cycle I and Cycle II can run well. In the first cycle of the first meeting, the teacher's activity scored 14 or 67% in the good category. Teachers’ activity was increased at the next meeting, which the score is 16 with a percentage of 76% at the second and third meetings. The scoring shows that the learning given by teacher belonging to excellent category. Whereas in the second cycle, each meeting obtained a score with a very good category, namely a score of 18 or 86% in the first and second meetings, and a score of 19 with a percentage of 90% in the third meeting. From the research data obtained it was concluded that there has been an increasing in science ability of Grade IV students in Force subject matter through the using of multiple intelligence methods in SD Negeri Parakan, Pamulang District, South Tangerang City.